2020
DOI: 10.3390/cells9081813
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2 Expression as a New Hallmark of Advanced Endometriosis

Abstract: Recent evidence suggests that immunological aspects play a pivotal role in this disorder. Toll-like receptor 2 (TLR2) is crucial in recognizing microbial infections and mediating innate immune response. The objective of our study was to rate with flow cytometry the levels of several subsets of dendritic cells, monocytes, and basic peripheral blood lymphocytes expressing TLR2, aiming at the determination of a possible correlation between the expression of TLR2 and the clinical outcomes of endometriosis in 40 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…A significant number of papers did not consider the menstrual cycle phase in their analysis. Investigators identified comparable findings with no difference in CD8 T cell proportions among leukocytes between endometriosis and control group (29.3 ± 5.5 vs 30.2 ± 4.9, respectively) and no difference in CD4/CD8 ratio (1.4 (0.73–2.7) vs 1.3 (0.93–4.5), respectively) ( 49 ). Interestingly, no difference was observed even when they compared CD8 T rates and CD4/CD8 ratio between different disease stages.…”
Section: Resultsmentioning
confidence: 96%
“…A significant number of papers did not consider the menstrual cycle phase in their analysis. Investigators identified comparable findings with no difference in CD8 T cell proportions among leukocytes between endometriosis and control group (29.3 ± 5.5 vs 30.2 ± 4.9, respectively) and no difference in CD4/CD8 ratio (1.4 (0.73–2.7) vs 1.3 (0.93–4.5), respectively) ( 49 ). Interestingly, no difference was observed even when they compared CD8 T rates and CD4/CD8 ratio between different disease stages.…”
Section: Resultsmentioning
confidence: 96%
“…Notably, TLR-2, which is essential in the innate immune system, was upregulated in the myeloid dendritic cells and B cells in patients with endometriosis. TLR-2 has been proposed as a potential noninvasive biomarker ( 168 ).…”
Section: The Effect Of Regulating the Immune Microenvironment Of Endo...mentioning
confidence: 99%
“…TLR2 plays a role in bacterial infections and the innate immune system. Its expression has been assessed in endometriosis patients, but further research is needed to understand its specific involvement [ 71 ]. Overall, more studies are needed to explore the presence and potential use of TLRs as biomarkers for the early detection of endometriosis.…”
Section: The Importance Of Disorders Of Immune Homeostasis In the Pat...mentioning
confidence: 99%